"See and Treat": spreading like wildfire? A qualitative study into factors affecting its introduction and spread. Issue 8 (26th July 2005) - Lamont, S Saint
Abstract : Objectives: The aim of this paper was to explore key factors that influenced the spread of "See and Treat" in a range of accident and emergency (A&E) departments. Methods: The study adopted a qualitative approach, and semi-structured interviews were undertaken with 21 key individuals working across 10 A&E departments operating See and Treat. Participants included clinicians, managers, and chief executives. Results: Many factors influenced the spread of See and Treat. The initiative was well supported and monitored by external agencies, patients benefited and no staff groups lost out, waiting times were reduced, and Department of Health targets were achieved. However, this study indicates there were also a range of factors that limited the spread of See and Treat, including lack of additional resources and suitably experienced staff, impact upon quality of care, and no prior evaluation of its benefits. An interesting additional factor that may be both facilitating and limiting is the complexity of the A&E culture, in particular staff perspectives about working with minor injuries. Conclusions: See and Treat was promoted as a solution to waiting times problems in A&E, without evidence from any national evaluation. However, many staff members referred to its usefulness as a tool to reduce waiting times and enhance the patient journey, although resource, quality, and staffing issues may mean such an initiative may be difficult to sustain in its present form.